The Natural Monopoly effect in brand image associations. Issue 4 (November 2017) - Stocchi, Lara; Pare, Vipul; Fuller, Rachel; Wright, Malcolm
Highlights: The Natural Monopoly pattern is present in brand image associations. This is consistent with buying behaviour and stable over time. More popular brands monopolise the majority of associations with category cues or category entry points in the mind of consumers. To increase the level of mental availability, popular brands need to reach out to consumers with limited knowledge of the category; less popular brands need to build and reinforce associations with category cues. Abstract: The Natural Monopoly is a robust empirical generalisation that describes the tendency for more popular brands to attract light users of the product category. This study shows that this pattern can also explain the underlying 'trade-off' between associations that consumers hold in memory for a specific brand vs. other brands, given the same range of category cues or category entry points (e.g., purchase or consumption situations, core benefits etc.). Specifically, the Natural Monopoly can be extended to explain that consumers with limited knowledge of brands are more likely to memorise associations primarily in relation to the most popular brands of the category, which 'monopolise' category entry points. This is confirmed with broadly consistent results across three data sets, multiple time-periods and a total of six categories (including CPGs, services and mobile applications). As such, this study significantly expands the generalisability of the Natural Monopoly empirical law by showcasing it as a 'tool' to extend knowledge on brand image associations. The results also yield important practical implications for growing a brand's mental availability. For the most popular brands, the outcomes of this study highlight the relevance of reaching out to consumers with limited knowledge of brands within the same category; for the least popular brands, they indicate the importance of building associations with category entry points. Chinese Abstract: 自然垄断是一个强大的实证概化理论，描述了热门品牌吸引同产品类别中轻度用户的趋势。本研究表明，这种模式也可以解释消费者面对相同的类别提示或类别入口（如购买或消费情景，核心利益等）时，脑中对于特定品牌的印象和其他品牌的潜在的"取舍"。具体来说，自然垄断可以扩展并解释，对于品牌认知有限的消费者更有可能记得该类别里最流行的品牌的联想，而这就"垄断"了类别的入口。这一观点通过三个数据集、多时间段和总共六个产品类别（包括快速消费品、服务和移动应用）的广泛一致结果而得到证实。因此，本研究显著地扩展了"自然垄断"经验法则的广泛性，可以作为有力的工具，为现有的品牌形象关联实证知识再增光彩。研究结果也具有重要的实践意义，有助于增加品牌的心智显著性。对于最受欢迎的品牌，本研究的结果强调了应当去接触对同类品牌认知有限的消费者们；对于最不受欢迎的品牌，文章指出了与类别入口建立联系的重要性。